Impact of airport processing factors on airportservice performance in Abu Dhabi International Airport - Bintarish Almheiri, Mansour Mohamed Obaid (2023)
Improving airport service performance for travelers is essential to gaining a significant foothold in today's competitive airport environments. The study tests the significant relationship between waiting time, excellent service, safe screening, and service performance at Abu Dhabi International Airport in the United Arab Emirates (UAE). The study bridged the gaps and enabled this study of the effectiveness of Abu Dhabi airport context in both the existing evidence and its practical applications. To achieve this goal, the research explored the following objectives: assessing the impact of passenger waiting time on service performance at Abu Dhabi International Airport, evaluating the impact of excellent service on service performance at Abu Dhabi International Airport, and evaluating the impact of safe screening on service performance at Abu Dhabi International Airport. The study used a quantitative research approach for the collection of data from four hundred passengers have been surveyed at the Abu Dhabi International Airport. The total number of responses received was 327, although only 230 (57%) were considered for the PLS-SEM analysis. The results of the current study revealed a significant effect of queuing time, prime services, and secure screening on service performance. The findings of this study are expected to assist Abu Dhabi International Airport management in formulating effective measures for the enhancement of airport service performance for passengers. The current study also emphasized the research's limitations, implications, and future studies suggestions.